Proteomic characterization of molecular mechanisms of paraquat-induced lung injury in a mouse model - Yu Qing Zhou; Jin Jin Peng; Li Ping Shan; Wei Liu (Respiratory Research, 2025)
Abstract Background We sought to explore the molecular mechanisms underpinning acute lung injury (ALI) caused by poisoning with paraquat (PQ). Methods Selection mice were intraperitoneally injected with PQ at 40 mg/kg, whereas controls were injected with sterile saline. On days 2, 7, and 14 after administration, mice were anesthetized and sacrificed, and lung tissue was removed. Lung pathological changes were observed with conventional staining techniques. Lung tissue components were assessed with tandem mass spectrometry tag technology, and differentially expressed proteins (DEPs) were bioinformatically analyzed and investigated with parallel reaction monitoring. Results The expression of 91, 160, and 78 proteins was significantly altered at days 2, 7, and 14, respectively. Gene Ontology analyses revealed that the DEPs in the PQ-2d and PQ-7d groups were involved primarily in humoral immunity and coagulation-related reactions, whereas those in the PQ-14d group were implicated primarily in chemotactic and regulatory responses. Kyoto Encyclopedia of Genes and Genomes analyses indicated that complement and coagulation cascades were key pathways in the PQ-2d and PQ-7d groups, whereas xenobiotic metabolism by cytochrome P450 was a key pathway in the PQ-14d group. Nine proteins at PQ-2d and eight proteins at PQ-7d were validated through parallel reaction monitoring (PRM). Conclusions PQ-induced ALI depends on over-activation of immune responses by damaged alveolar/endothelial cells, and the complement/coagulation cascade pathway plays a key role during this process. The proteins identified herein might provide new therapeutic targets or biomarkers for PQ poisoning.